2018
DOI: 10.1080/10826084.2017.1416402
|View full text |Cite
|
Sign up to set email alerts
|

European University Students' Experiences and Attitudes toward Campus Alcohol Policy: A Qualitative Study

Abstract: Students will not support an on campus alcohol restriction and a policy should therefore focus on prevention initiatives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 6 publications
0
5
1
1
Order By: Relevance
“…A difference between previous studies and our study is that in the context of year level, students in South Korea have the highest AUDIT-C scores in their freshman year, whereas students in international studies mostly consume high amounts of alcohol during their sophomore and junior years [3,13,32,33]. This phenomenon may be particular to South Korea; students in South Korea have been noted to consume the most amount of alcohol in their freshman year (often, unwillingly) at various orientation, and/or freshmen events where juniors and seniors pressure incoming students to drink [1].…”
Section: Discussioncontrasting
confidence: 93%
See 2 more Smart Citations
“…A difference between previous studies and our study is that in the context of year level, students in South Korea have the highest AUDIT-C scores in their freshman year, whereas students in international studies mostly consume high amounts of alcohol during their sophomore and junior years [3,13,32,33]. This phenomenon may be particular to South Korea; students in South Korea have been noted to consume the most amount of alcohol in their freshman year (often, unwillingly) at various orientation, and/or freshmen events where juniors and seniors pressure incoming students to drink [1].…”
Section: Discussioncontrasting
confidence: 93%
“…Similar trends were also found among some Asian countries like China [32] and Taiwan [34], where alcohol use was greatest among 1st year students. However, in most European countries like France [33], Belgium, Colombia, Ireland, and Poland [3,4] age and/or year of study were not associated with binge drinking and associated drinking behaviors.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…They found that 85% of new students reported consuming alcohol during Orientation Week and that students consumed significantly more during Orientation Week than before university (9 vs. 19 drinks). Indeed, qualitative studies suggest that new students view drinking as the point of Orientation Week and advertising (e.g. flyers for clubs) may actively promote drinking .…”
Section: ‘The Rabbit Hole’mentioning
confidence: 99%
“…Det er godt dokumentert at studenter er en gruppe som har et høyt alkoholinntak, spesielt under fadderuken (Myrtveit et al, 2016;Tefre, Amundsen, Nordlund & Lund, 2007;Van Hal et al, 2018). Samtidig viser andre studier en sammenheng mellom deltakelse på fadderuken og grad av sosial inkludering, trivsel og etablering av nye vennskap (Knapstad, 2018;Myrtveit, Askeland, Knapstad, Knudsen & Skogen, 2017;Stålesen, 2015;Vaadal, 2014).…”
Section: Introduksjonunclassified